Therapies for Mitochondrial Disorders - Kayli Sousa Smyth; Anne Mulvihill (SURE Journal: (Science Undergraduate Research Experience Journal))
Mitochondria are cytoplasmic, double-membrane organelles that synthesise adenosine triphosphate (ATP). Mitochondria contain their own genome, mitochondrial DNA (mtDNA), which is maternally inherited from the oocyte. Mitochondrial proteins are encoded by either nuclear DNA (nDNA) or mtDNA, and both code for proteins forming the mitochondrial oxidative phosphorylation (OXPHOS) complexes of the respiratory chain. These complexes form a chain that allows the passage of electrons down the electron transport chain (ETC) through a proton motive force, creating ATP from adenosine diphosphate (ADP). This study aims to explore current and prospective therapies for mitochondrial disorders (MTDS). MTDS are clinical syndromes coupled with abnormalities of the ETC and OXPHOS, caused by pathogenic variants in mtDNA or nDNA. Many MTDS emerge from either homoplasmic or heteroplasmic mutations of the DNA, and include mitochondrial encephalomyopathy, lactic acidosis and stroke-like episodes. Current therapies include increasing mitochondrial biogenesis, the use of antioxidants, dietary approaches, and exercise. However, these are mostly symptomatic and supportive therapies. Future therapies comprise of personalised and precision medicine approaches which include gene, mitochondrial, cell, and in utero-based therapies. Obstacles towards discovering effective therapies include the rarity of MTDS, its pathogenic complexity and lack of clinical trials. Despite the lack of current curative therapies for MTDS, emerging therapies promise exciting and clinically meaningful therapies in the future.